Examining the influence of urban form on the thermal comfort of street canyons in Tehran: a case study of Narmak neighbourhood - Salmanian, Mohammadhassan; Mousavi, Mirhassan; Nasirimehr, Parisa; Takhmiri, Hedieh; Ujang, Norsidah; Shahidan, Mohd Fairuz; Dahlan, Nur Dalilah (IIUM Press, 2024)
As urbanization advances, the emphasis on outdoor spaces grows, highlighting poor thermal balance as a detrimental factor in achieving comfort within densely populated urban structures. Consequently, an urgent imperative exists to evaluate and optimize urban morphology to ensure sufficient outdoor thermal comfort. This study assesses the thermal efficiency of residential areas in Narmak, Tehran, Iran, with the primary goal of enhancing thermal comfort, specifically the PET, and discerning optimal urban layouts. Employing computational simulation techniques, this investigation meticulously examines urban design variables that influence outdoor thermal comfort, encompassing street direction, enclosure, building forms’ typology, and tree planting. The research findings unveil that the orientation of street canyons exerts the most significant influence at 39.12%, closely followed by the aspect ratio at 36.78%. Remarkably, within the considered climatic components such as air temperature, wind speed, and humidity, tree planting emerges as the most influential factor impacting outdoor thermal comfort in this case study. These analytical outcomes furnish valuable insights into the contextual design of elements that influence the thermal comfort of outdoor open spaces.